An Ibero-American inter-laboratory trial to evaluate serological tests for the detection of anti-Neospora caninum antibodies in cattle - Campero, Lucía María (2017)
We carried out an inter-laboratory trial to compare the serological tests commonly used for the detection of specific Neospora caninum antibodies in cattle in Ibero- American countries. A total of eight laboratories participated from the following countries: Argentina (n = 4), Brazil (n = 1), Peru (n = 1), Mexico (n = 1), and Spain (n = 1). A blind panel of well-characterized cattle sera (n = 143) and sera representative of the target population (n = 351) was tested by seven in-house indirect fluorescent antibody tests (IFATs 1–7) and three enzyme-linked immunosorbent assays (ELISAs 1–3; two in-house and one commercial). Diagnostic performance of the serological tests was calculated and compared according to the following criteria: (1) the BPre-test information,^ which uses previous epidemiological and serological data; (2) the BMajority of tests,^ which classifies a serumas positive or negative according to the results obtained by most tests evaluated. Unexpectedly, six tests showed either sensitivity (Se) or specificity (Sp) values lower than 90%. In contrast, the best tests in terms of Se, Sp, and area under the ROC curve (AUC) values were IFAT 1 and optimized ELISA 1 and ELISA 2. We evaluated a high number of IFATs, which are the most widely used tests in Ibero-America. The significant discordances observed among the tests regardless of the criteria employed hinder control programs and urge the use of a common test or with similar performances to either the optimized IFAT 1 and ELISAs 1 and 2.